2022
DOI: 10.31662/jmaj.2021-0201
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Physical Therapy: A Position Paper by the Physical Therapist Section of the Japanese Association of Rehabilitation Nutrition (Secondary Publication)

Abstract: Several patients undergoing physical therapy have nutritional problems. Knowledge of nutrition is necessary for addressing nutritional problems, such as malnutrition, sarcopenia, frailty, and cachexia. However, the relationship between physical therapy and nutrition is not fully understood. Physical therapy plays an important role in nutritional management, and evaluations, such as muscle strength and muscle mass evaluations, play an important role in nutritional screening and diagnosis. Exercise, as the core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…One possible reason for this result is the difference in physical functioning between community-dwelling and inpatients [ 16 , 31 ]. Participants who were hospitalized for rehabilitation often had decreased physical function, and we also excluded patients with higher physical function (i.e., SPPB ≥ 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason for this result is the difference in physical functioning between community-dwelling and inpatients [ 16 , 31 ]. Participants who were hospitalized for rehabilitation often had decreased physical function, and we also excluded patients with higher physical function (i.e., SPPB ≥ 10).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another systematic review suggested that exercise and nutrition interventions may be useful in improving physical function in patients with sarcopenia [ 15 ]. Therefore, management of physical exercise and nutrition in patients undergoing rehabilitation is important [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional physical therapy overlaps with rehabilitation nutrition, and the two concepts share goals, assessment, and intervention strategies. The practice of these two concepts requires both perspectives [ 30 ]: physical therapy that considers nutrition status and nutritional care management that maximizes the effectiveness of physical therapy. Exercise therapy consists of flexibility exercises, resistance training, and aerobic training.…”
Section: Rehabilitation Nutritionmentioning
confidence: 99%
“…Exercise load settings are determined using subjective exercise intensity (Borg scale) and other factors, and exercise frequency, intensity, and duration are adjusted. Exercise and nutrition therapy are effective, however few reports exist on the effectiveness of nutritional physiotherapy [ 30 ]. In addition, systematic clinical practice based on a bi-directional nutrition and physical therapy perspective is limited.…”
Section: Rehabilitation Nutritionmentioning
confidence: 99%
See 1 more Smart Citation